Investigation of biochemical responses of Bacopa monnieri L. upon exposure to arsenate. Issue 8 (7th June 2011) - Mishra, Seema; Srivastava, Sudhakar; Dwivedi, Sanjay; Tripathi, Rudra Deo
<x xml:space="preserve">Abstract</x> Widespread contamination of arsenic (As) is recognized as a global problem due to its well‐known accumulation by edible and medicinal plants and associated health risks for the humans. In this study, phytotoxicity imposed upon exposure to arsenate [As(V); 0–250 μM for 1–7 days] and ensuing biochemical responses were investigated in a medicinal herb Bacopa monnieri L. vis‐à‐vis As accumulation. Plants accumulated substantial amount of As (total 768 μg g−1 dw at 250 μM As(V) after 7 days) with the maximum As retention being in roots (60%) followed by stem (23%) and leaves (17%). The level of cysteine and total nonprotein thiols (NP‐SH) increased significantly at all exposure concentrations and durations. Besides, the level of metalloid binding ligands viz., glutathione (GSH) and phytochelatins (PCs) increased significantly at the studied concentrations [50 and 250 μM As(V)] in both roots and leaves. The activities of various enzymes viz., arsenate reductase (AR), glutathione reductase (GR), superoxide dismutase (SOD), guaiacol peroxidase (GPX), ascorbate peroxidase (APX), and catalase (CAT) showed differential but coordinated stimulation in leaves and roots to help plants combat As toxicity up to moderate exposure concentrations (50 μM). However, beyond 50 μM, biomass production was found to decrease along with photosynthetic pigments and total soluble proteins, whereas lipid peroxidation increased. In conclusion, As accumulation potential of Bacopa may warrant its use as a phytoremediator but if Bacopa growing in contaminated areas is consumed by humans, it may prove to be toxic for health. © 2011 Wiley Periodicals, Inc. Environ Toxicol 28: 419–430, 2013.